Kenaf Fibre Reinforced Polypropylene Composites: Effect of Cyclic Immersion on Tensile Properties - W. H. Haniffah; S. M. Sapuan; K. Abdan; M. Khalid; M. Hasan; M. Enamul Hoque (International Journal of Polymer Science)
This research studied the degradation of tensile properties of kenaf fibre reinforced polypropylene composites due to cyclic immersion into two different solutions, as well as comparison of the developed composites’ tensile properties under continuous and cyclic immersion. Composites with 40% and 60% fibre loadings were immersed in tap water and bleach for 4 cycles. Each cycle consisted of 3 days of immersion and 4 days of conditioning in room temperature (28°C and 55% humidity). The tensile strength and modulus of composites were affected by fibre composition, type of liquid of immersion, and number of cycles. The number of immersion cycles and conditioning caused degradation to tensile strength and modulus of kenaf fibre reinforced polypropylene composites. Continuous and cyclic immersion in bleach caused tensile strength of the composites to differ significantly whereas, for tensile modulus, the difference was insignificant in any immersion and fibre loadings. However, continuous immersion in the bleach reduced the tensile strength of composites more compared to cyclic immersion. These preliminary results suggest further evaluation of the suitability of kenaf fibre reinforced polypropylene composites for potential bathroom application where the composites will be exposed to water/liquid in cyclic manner due to discontinuous usage of bathroom.